An Applied of Reward and Punishment Approach in English Learning Classroom - Bambang Nur Alamsyah Lubis; Khairun Niswa; Azizah Husda; Dinda Sapira (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2022)
This study aimed to describe an applied of reward and punishment in the learning process. The objectives of the study were to describe the application of reward and punishment in learning English at eight grades SMP Swasta Dharma Pancasila Medan, to describe students' responses to the implementation of rewards and punishments in learning English at eight grades SMP Swasta Dharma Pancasila Medan. This study used descriptive qualitative research design. The data of this study was result of observation and questionnaire. The source of the data was eight grade students at SMP Swasta Dharma Pancasila Medan. The researcher is the key instrument of this research and questionnaire sheet as supporting instrument. The results of the study, there were some kinds of reward and punishment that were applied by teacher in the classroom, such as giving several gift, giving applause, giving expressions, and giving points from the teacher to students (reward), and giving warning expressions, singing in front of the class, and squatting (punishment).